BIOCHEMICAL COMPOSITION AND ANTIOXIDANT PROFILE OF GEOGRAFICALLY LABELED KOHNU GRAPE (Vitis vinifera L.) CULTIVAR FROM TURKEY - Akbaba, Emel; Aydin, Sevinc; Sanyurek, Nesrin Karaca (Parlar Scientific Publications (P S P), 2021)
Vitis vinifera L. is cultivated throughout the World including Turkey which is one of the largest producers of grape. Grape is consumed as fresh or dry fruit as well as used in the wine industry in which good quality of grapes are preferred. Grape is also a part of the traditional Mediterranean diet which is linked to a low risk of cardiovascular and degenerative diseases. Kohnu is a geographically labeled type of grape cultivated in the eastern cities of Turkey. In this study, Kohnu grapes harvested from two different cities of Turkey were compared through phenolic compounds, phytosterols, vitamins, fatty acids, and antioxidative properties. The concentrations of phenolic compounds in the sample from Elazig were obtained to be significantly higher as compared to the sample from Malatya. Especially vanillic acid was found to be much higher in Elazig samples. The concentrations of fatty acids especially palmitic acid, palmitoleic acid, oleic acid, and linoleic acid were obtained significantly higher in Elazig samples as compared to Malatya samples. Vitamin and phytosterol concentrations of the samples from Elazig were also determined as higher as compared to Malatya samples. Significantly higher antioxidant activity of Kohnu grape seeds from Elazig was obtained via DPPH radical scavenging activity and MDA levels. The antioxidant profile of Kohnu grape seeds of Elazig samples could be related to phenolic composition and vitamins.
Keywords: Geografically labeled; Vitis vinifera L.; phenolics; fatty acids; antioxidant